Application of Individual Counseling with Systematic Desentization Techniques to Overcome Ailurophobia - Crisna, Ade; Suryati, Suryati; Fitri, Hartika Utami; Ariyati, Ika; Nurulbahiah, Nurulbahiah (Scidacplus, 2024)
This research contains problems related to: fear or anxienty about Ailurophobia, excessive feelings when in direct contact with cats in client “T”, and how to apply individual counseling using systematic desensitization techniques to overcome Ailurophobia so that client “T” gets counseling services in order to solve the problem Client “T” against Ailurophobia. This type of research is field research, the approach used is a qualitative approach case study design, and according to Creswell, it is a complex picture, examining words, detailed reports from the respondents’ views, and conducting studies in natural situations. The data colletion techniques used were observation and interviews. While data analysis techniques consist of pattern matching and time series analysis. The result of the research obtained were that client “T” was experiencing Ailurophobia with excessive fear and anxiety regarding Systematic Desensitization. Client “T” had improved regarding Ailurophobia. The factor causing Ailurophobia in client “T” is a feeling of trauma at elementary school (SD) level with a cat, such as bites and scratches received.